Biologic therapies for juvenile arthritis. Issue 3 (1st March 2003) - Wilkinson, N; Jackson, G; Gardner-Medwin, J
Abstract : A group of therapies with exciting potential has emerged for children and young people with severe juvenile idiopathic arthritis (JIA) uncontrolled by conventional disease modifying drugs. Theoretical understanding from molecular biologic research has identified specific targets within pathophysiological pathways that control rheumatoid arthritis (RA) and JIA. This review identifies the pathways of autoimmunity to begin to show how biologic agents have been produced to replicate, mimic, or block culpable molecules and so promote or inhibit cellular activity or proliferation. Of these agents, cytokine antagonists have shown greatest promise, and early clinical studies of tumour necrosis factor (TNF) blockade have identified dramatic clinical benefit in many children with JIA. However, as will also be discussed, overlap of pathways within a complex immune system makes clinical response unpredictable and raises additional ethical and administrative concerns.